Computational design of a two-photon excited FRET-based ratiometric fluorescent Cu2+ probe for living cell imaging. Issue 119 (17th November 2015) - Wang, Dan; Ren, Ai-Min; Guo, Jing-Fu; Zou, Lu-Yi; Huang, Shuang
Abstract : A novel TP FRET ratiometric fluorescent probe2a for Cu 2+ is designed.2a has a large TPA peak in the near-infrared light region and its energy transfer efficiency is nearly 100%. Abstract : Though copper ion (Cu 2+ ) is a widely distributed pollutant in the water environment, it plays a vital role in many biological processes. Hence, rapid detection and identification of Cu 2+ are important. In the past few years, fluorescence sensing has become the golden standard to detect Cu 2+, due to its high sensitivity, high selectivity, and useful applications in biology, medicine, environment and chemistry. Thus, researchers have widely concerned with the design and synthesis of Cu 2+ fluorescent probes. In this study, a novel probe2a with high sensitivity and selectivity for detecting Cu 2+ is designed. It is illustrated that2a is a ratiometric fluorescent probe, which recognizes Cu 2+ by a Förster resonance energy transfer (FRET) mechanism. Meanwhile, the two-photon absorption (TPA) optical properties of2a are calculated. The calculated results demonstrate that2a possesses a higher energy transfer efficiency upon excitation and a larger TPA peak in the near-infrared region than others. Therefore, it can be inferred that the probe2a should be an excellent two-photon (TP) excited FRET-based ratiometric fluorescent probe for Cu 2+ . The detailed investigations can provide a theoretical basis to synthesize copper-ion-responsive TP FRET-based ratiometric fluorescent reagents, which are powerful tools for the two-photon microscopy (TPM) and biological imaging of Cu 2+ in vivo .